2023
DOI: 10.3389/fimmu.2023.1102778
|View full text |Cite|
|
Sign up to set email alerts
|

T lymphocyte cell: A pivotal player in lung cancer

Abstract: Lung cancer is responsible for the leading cause of cancer-related death worldwide, which lacks effective therapies. In recent years, accumulating evidence on the understanding of the antitumor activity of the immune system has demonstrated that immunotherapy is one of the powerful alternatives in lung cancer therapy. T cells are the core of cellular immunotherapy, which are critical for tumorigenesis and the treatment of lung cancer. Based on the different expressions of surface molecules and functional point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 184 publications
0
4
0
Order By: Relevance
“…Tc1 cells constitute the most prevalent subset of tumorinfiltrating lymphocytes in multiple types of cancers, including lung cancers 20 , breast cancers 21 , and chronic lymphocytic leukemia 22 , and are associated with favorable prognoses [23][24][25][26][27] . Tumors exhibiting a high degree of infiltration by Tc1 cells that subsequently produced elevated levels of IFN-γ are referred to as "hot" tumors.…”
Section: Cytotoxic Cd8 + T Cells (Tc1 Cells)mentioning
confidence: 99%
“…Tc1 cells constitute the most prevalent subset of tumorinfiltrating lymphocytes in multiple types of cancers, including lung cancers 20 , breast cancers 21 , and chronic lymphocytic leukemia 22 , and are associated with favorable prognoses [23][24][25][26][27] . Tumors exhibiting a high degree of infiltration by Tc1 cells that subsequently produced elevated levels of IFN-γ are referred to as "hot" tumors.…”
Section: Cytotoxic Cd8 + T Cells (Tc1 Cells)mentioning
confidence: 99%
“…Activated RhoA leads to the formation of stress fibers within cells and expression of chemokines, cytokines, and growth factors [54,55]. The important role of immune function in the incidence and development of lung cancer is well established [56][57][58]. As reported, fermented cordyceps powder reduces radiation-induced bone marrow suppression, increases the percentage of peripheral blood leukocytes, improves chemotherapy tolerance, and promotes spleen cell proliferation, NK cell activity, and T-helper cytokine secretion in mice with impaired immune function [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a larger population of Tregs in this microenvironment was found to be linked with a detrimental prognosis [33,34]. It has been demonstrated that T, B lymphocytes, and NK cells (collectively referred to as TBNK) play a role in combating tumors within the lung tumor environment [35][36][37].…”
Section: Discussionmentioning
confidence: 99%